Collaborative Governance:: Implementation of Regional Regulation Number 7 of 2019 Concerning Port Services Retribution - Gazalin, Junaid; Rijal, Hairul; Roy, Rismal Saktiawan Bin (Indonesian Research Journal on Education, 2025)
This Study aims to analyze the role of collaborative governance in the implementation of regional regulations policies towards increasing  the income of regional own-source revenue in South Buton Regency. This Study uses a type of qualitative research with data collection  through observation, interviews, documentation, literature studies and questionnaires. The problem arises because the actual amount of port levies from 202 and 2021 is quite small, namely IDR 5.518.000 and IDR 4.615.000 for targets of  IDR 7.000.000 and IDR 10.000.000. From the two years of impelementing this regulation, it has decreased significantly. The results showed that the collaboration between the South Buton Regency Transportation Service and the South Buton Regency Regional Revenue Agency in implementing Regional Regulation Number 7 of 2019 has not gone well,  factors that influence policy implementation such as communication, resources, disposition, organizational structure. has not been running well, smoothly and has many obstacles.To overcome the problem of regional fees experienced by the South Buton Regency Transportation Service, in 2023 the South Buton Regency Regional Revenue Agency will hold 3 coordination meetings on regional taxes and fees, which will be held in April, May and June. The purpose of holding this coordination meeting is to strengthen the collaboration of each OPD of South Buton district in managing, solving problems and finding solutions to regional tax and retribution issues in South Buton.